Die rol van kognitiewe funksionering in hoop by adolessente - Venter, Alet (University of the Free State, 2004)
The primary aim of this research was to clarify the cognitive function of hope in adolescents. The hope construct was theoretically investigated in this research and an integrated hope model and hope process were developed. The nature of hope was investigated in adolescents (boys and girls respectively). Hope is furthermore described (for the purpose of this study) as a mood condition which activates emotions. A cognitive process starts when pathway thoughts (the setting of objectives) and work agency thinking (motivation) take place. Cognitive function in hope is discussed by means of describing cognitive styles. The connection between cognitive styles and hope is further investigated and also related to cognitive development in adolescents. Specific attention is paid to hope and the adolescent in the South African context. During the empirical study, the cluster sampling method was used to identify four schools in the North West Province which would participate in this research. All the grade 12 learners of those specific schools were approached to complete questionnaires. The study group consisted of 485 adolescents. In this research, hope was determined by the Hope Scale of Snyder et al. (1991a) and cognitive function by means of the Constructed Thinking Inventory (Epstein, 1993) and the Cognitive Flexibility Scale (Martin & Rubin, 1995), respectively. Good reliability indices were obtained for all the questionnaires and scales used. Five variables, namely cognitive flexibility, naïve optimism, esoteric thinking, personal beliefs (superstition) and behaviour coping, contribute considerably to the clarification of the variance of the pathway component of hope in adolescents. As far as culture and cognitive functioning were concerned, definite differences between score averages were obtained on four scales of the two culture groups. These scales were global constructive thinking, esoteric thinking, naïve optimism and cognitive flexibility. Afrikaans-speaking adolescents obtained a higher average score than the Africanlanguage adolescents on the scale of global constructed thinking. Concerning the scales of esoteric thinking, naïve optimism, and cognitive flexibility the Africanlanguage adolescents obtained a higher average score than the Afrikaans-speaking adolescents. The higher average score of the African-language adolescents indicates lower cognitive flexibility. However, it is important to take into account that the cognitive flexibility scale is based on western culture. Despite the fact that the biographical variable, culture, does not considerably contribute to the clarification of the pathway component variance, it does contribute to the clarification of the agency component variance. As far as gender differences are concerned, the results of this study give no indication of any contribution to the clarification of the variance of the agency or the pathway components of hope. Obvious differences were evident concerning the average emotional coping and naïve optimism of the two sexes. Concerning the emotional-coping scale, the boys obtained a higher average score than the girls, while the girls obtained a higher average score than the boys on the scale naïve optimism. Recommendations for further research were made on the strength of the results.

Die primêre doel van hierdie navorsing was om kognitiewe funksie in hoop by adolessente te verklaar. Die konstruk hoop is in hierdie navorsing teoreties ondersoek en 'n geïntegreerde hoopmodel, asook 'n geïntegreerde hoopproses is ontwikkel. Die aard van hoop is by adolessente (onderskeidelik seuns en dogters) ondersoek. Verder is hoop is vir die doeleindes van hierdie studie as 'n gemoedstoestand beskryf wat emosies aktiveer. 'n Kognitiewe proses tree in werking wanneer fasiliteringsbaandenke (die stel van doelwitte) en werkbaandenke (motivering) plaasvind. Kognitiewe funksie in hoop is bespreek deur die beskrywing van kognitiewe style. Die verband tussen kognitiewe style en hoop is verder aangedui en ook in verband gebring met kognitiewe ontwikkeling by adolessente. Daar is spesifiek gelet op hoop en die adolessent in die Suid-Afrikaanse konteks. In die empiriese ondersoek is van die trossteekproeftrekkingsmetode gebruik gemaak om vier skole in die Noordwes-Provinsie te identifiseer, wat aan die navorsing sou meedoen. AI die graad 12-leerders van daardie spesifieke skole is genader om vraelyste te voltooi. Die ondersoekgroep het bestaan uit 485 adolessente. In hierdie navorsing is hoop bepaal deur die hoopskaal van Snyder et al. (1991) en kognitiewe funksie deur onderskeidelik die Kognitiewe denkevraelys (Epstein, 1993) en die Kognitiewe buigsaamheidsvraelys (Martin & Rubin, 1995). Goeie betroubaarheidsindekse is vir al die vraelyste en skale wat gebruik is, verkry. Vyf veranderlikes, naamlik kognitiewe buigsaamheid, naïewe optimisme, esoteriese denke, persoonlike bygelowige denke en gedrags-coping, lewer 'n beduidende bydrae tot die verklaring van die variansie van die fasiliteringsbaankomponent in hoop van adolessente. Met betrekking tot kultuur en kognitiewe funksionering, is beduidende verskille tussen die gemiddelde tellings op vier skale vir die twee kultuurgroepe verkry. Hierdie skale is globale konstruktiewe denke, esoteriese denke, naïewe optimisme en kognitiewe buigsaamheid. Ten opsigte van globale konstruktiewe denke het die Afrikaanssprekendes 'n hoër gemiddelde telling as die Afrikataalsprekendes verkry. Wat die skale esoteriese denke, naïewe optimisme en kognitiewe buigsaamheid betref, toon die Afrikataalsprekendes telkens 'n hoër gemiddelde telling as die Afrikaanssprekendes. Die hoër gemiddelde telling wat die Afrikataalsprekendes in vergelyking met die Afrikaanssprekendes behaal het op die skaal kognitiewe buigsaamheid is aanduidend van laer kognitiewe buigsaamheid. Dit behoort egter in ag geneem te word dat die kognitiewe buigsaamheidskaal vir die westerse kultuur ontwikkel is. Hoewel die biografiese veranderlike, kultuur, nie beduident bydra tot die verklaring van die variansie van die fasiliteringsbaankomponent nie, dra kultuur wel by tot die verklaring van variansie van die werkbaankomponent. Wat geslagsverskille betref, toon die resultate van hierdie studie geen bydrae tot die verklaring van die variansie van die werkbaankomponent sowel as van die fasiliteringsbaankomponent in hoop nie. Beduidende verskille is egter ten opsigte van die gemiddelde tellings vir emosionele coping en naïewe optimisme vir die twee geslagte verkry. Ten opsigte van die emosionele-copingskaal het die seuns 'n hoër gemiddelde telling as die dogters behaal, terwyl wat naïewe optimisme betref, die dogters weer 'n hoër gemiddelde telling as die seuns behaal het. Uit die resultate is aanbevelings vir verdere navorsing gemaak.
Thesis (Ph.D. (Psychology))--University of the Free State, 2004
Keywords: Hope; Integrated hope model; Integrated hope process; Cognitive style; Constructive thinking; Destructive thinking; Cognitive flexibility; Problem solving thinking; Adolescent; Cognitive functioning; South African context; Adolescent psychology; Hope -- Psychological aspects; Thought and thinking